The “Skull Flap” a new conceived device for decompressive craniectomy/cranioplasty: Feasibility study on cadaver specimen - Chibbaro, Salvatore (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Decompressive craniectomy (DC) is a procedure that is currently performed with increasing frequency. The reason is that its indications have become much broader. This procedure may be associated with the relevant morbidity in the postoperative stage due to the creation of a large bone defect. On the other hand, cranioplasty is associated too with some of the common complications related to any reconstructive head surgery. The authors present a newly developed device: The “Skull Flap” (SF). This new device allows the surgeon to complete a DC, yet providing at the same time a cranial reconstruction that will not require the patient to undergo a second reconstructive procedure. MATERIALS AND METHODS: Different size and location craniectomies were carried out on four human cadaveric heads; the bone flaps were then repositioned in a more elevated position with respect to the skull edges. The flaps were placed at a distance of 12 and 15 mm from the skull edges using the SF system. Crash tests were conducted on each flap while in open and closed positions to assess its reliability and efficacy. RESULTS: SF was shown to be a strong fixation device that allows satisfactory brain decompression by keeping the original bone flap away from the swollen brain; at the same time, in a later stage, it allows cranial reconstruction in a simple way. CONCLUSION: The SF device was shown to be very easy to use, adaptable, and practical to apply; thus, allowing both satisfactory brain decompression as well as bone flap repositioning at a later time after the brain swelling has subsided.